2022
DOI: 10.1007/s11356-022-20659-3
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printing of plasma surface–modified wool and cotton fabrics with plant-based inks

Abstract: In this research paper, sustainable technologies that are plasma surface treatment and digital printing of wool and cotton fabrics with herbal inks are implemented for ecological outcomes. One of the significant objectives was to study the plasma surface modification and its implication on fabric absorbency, K/S values gained, and the fastness properties of the resultant herbal fabrics. The wash fastness to colour change was studied wherein plasma surface treatment remarkably improved wash fastness ratings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, it is expected that CRE would not be viewable on absorptive fabric surface on Scanning Electron Microscope (SEM), unlike inkjet printed solid surface of photonics. The study presented here is in connection with the research by the authors on herbal ink formulation and inkjet printing of plasma surface modi ed wool and cotton fabric with herbal inks (Thakker, Sun, & Bucknall, 2022). The focus of this paper is the assessment of the quality of print and the coffee-ring effect illustrated on wool and cotton fabrics inkjet-printed with herbal inks.…”
Section: Thermal Print Headmentioning
confidence: 95%
See 1 more Smart Citation
“…However, it is expected that CRE would not be viewable on absorptive fabric surface on Scanning Electron Microscope (SEM), unlike inkjet printed solid surface of photonics. The study presented here is in connection with the research by the authors on herbal ink formulation and inkjet printing of plasma surface modi ed wool and cotton fabric with herbal inks (Thakker, Sun, & Bucknall, 2022). The focus of this paper is the assessment of the quality of print and the coffee-ring effect illustrated on wool and cotton fabrics inkjet-printed with herbal inks.…”
Section: Thermal Print Headmentioning
confidence: 95%
“…Therefore, preferentially sourced for the study. Plant-based inks were formulated from the selected plant materials, following the recipe (Stoichiometry and methodology) formulated by Thakker and Sun(Thakker, Sun, & Bucknall, 2022).…”
mentioning
confidence: 99%
“…Therefore, preferentially sourced for the study. Plant-based inks were formulated from the selected plant materials, as revealed in Figure 7 following the recipe (Stoichiometry and methodology) formulated by Thakker and Sun (Thakker, Sun, & Bucknall, 2022). The lab dips provided the colour values as illustrated in Tables 4 and 5.…”
Section: Materials Plant-based Biomaterialsmentioning
confidence: 99%
“…Only a small number of reports in the literature consider textile dyeing. For instance, a study by Thakker et al investigated how plasma surface modification improved the fabric absorbency, color strength, and fastness properties of wool and cotton fabrics which were digitally printed with quebracho-containing ink [41]. Another study by Alves et al suggested using quebracho extract (Schinopsis spp.)…”
Section: Introductionmentioning
confidence: 99%